Analisis Faktor-Faktor Keselamatan dalam Bernavigasi Kapal Kecepatan Tinggi di Traffic Separation Scheme (TSS) - Widodo, B.L Hentri; Wahyuni, Eni Tri; Rubiyanto, Aan (JURNAL BARTEK, 2026)
The causes of ship collisions while navigating TSS (Traffic Separation Schemes) are caused by various factors including the ship's own crew, environmental factors, equipment factors and the application of high-speed ship operating standards. The main safety factor in navigation for high-speed ships is that the ship is manned by a crew that is competent in operating high-speed ships and is supported by equipment suitable for high-speed ships. The purpose of this paper is to analyze the factors that cause the risk of collisions for high-speed ships, the second is to analyze the main safety factors in navigating on traffic separation charts, and the third is how to increase the safety of high-speed ships when navigating. The method used is the literature review method. Namely by collecting several data sources from several scientific journals and from several studies and several books related to research material. The discussion obtained data on the causes of high-speed ship accidents when navigating on traffic separation charts and how to improve ship safety. The conclusion is that ship accidents can be minimized if the ship is manned by a competent crew, appropriate equipment and implementation of appropriate ship operating procedures.